Pelatihan Pembuatan Website Dengan CMS (Content Management System) Di Smk Muhammadiyah Karanganyar - Rahmad Ardhani; Ita Permatahati; Faiq Fadhil (Fakultas Teknik Universitas Cenderawasih, 2022)
Smk Muhammadiyah 02 Karangayar is one of the schools that follows technological developments by visiting schools through the website. SMK Muhammadiyah 02 Karangayar has a bold business and marketing major so that every student needs expertise in website creation as a form of keeping up with technological developments in the digital marketing era. Smk Muhammadiyah 02 Karangayar requires supporting training that improves students' ability to create websites.